Effectiveness of Long-Acting Injectable Antipsychotics in Schizophrenia: A Literature Review and Bayesian Meta-Analysis Informing Economic Considerations - Orietta Zaniolo; Gianni Ghetti; Massimiliano Povero; Lorenzo Pradelli (Farmeconomia: Health Economics and Therapeutic Pathways, 2019)
BACKGROUND: Although the use of long-acting injectable antipsychotics (LAIs) is considered an important option in the management of schizophrenia two recent meta-analysis, which aimed to compare LAIs vs oral antipsychotics (OAPs) in terms of relapse rate, showed discordant results. AIM: To investigate factors affecting the efficacy of antipsychotics in terms of relapse prevention in the real-world and to estimate the management cost of an episode of relapse. METHODS: We conducted a literature search using MEDLINE/PubMed with the aim to extract efficacy, effectiveness and adherence data of LAIs and OAPs. The primary outcome was the relative risk (RR) of relapse between two strategies. The extracted RR were included in a series of Bayesian statistical models based on the starting hypotheses. The RR rates obtained from the meta-analysis have been used as input for an economic evaluation of the total costs associated with the management of the patient with schizophrenia from the Italian NHS perspective. RESULTS: The literature search identified 34 studies which met the inclusion criteria and were analyzed. According to the model that best explains the data, in the real-world setting the effectiveness with LAIs is greater than with OAPs, with a more pronounced effect for SGAs than for FGAs. Taking into account generation, route and frequency of administration, the RR decreased with lower administration frequency, with SGA LAI administered once every 90 days which is associated with the greatest reduction in the risk of relapse (-85%). When the results of the meta-analysis are used to feed an economic evaluation the results show that the SGA administered every 90 days is the strategy with the least expected cumulative cost both at 1 (€ 3,509) and 5 years (€ 19,690). CONCLUSION: SGA LAIs administered every 90 days seems to be the best option for the treatment of patient with schizophrenia from both the clinical and economic perspectives.